Navigating bounded agency in exercising climate action: Insights from Malawian and Zambian university students (Journal of Student Affairs in Africa, 2025)
The pressing issue of climate change has galvanized a global movement, with young people at the forefront as vocal advocates for environmental action. However, various structural and institutional factors often constrain the ability of university student environmentalists to translate their concerns into meaningful action. Using the concept of bounded agency within the capability approach, this qualitative study explored the perspectives of students from two universities, one in Malawi and one in Zambia, to better understand the challenges and opportunities they encounter in their efforts to translate their environmental concerns into tangible outcomes.  The study reveals that while participants are deeply committed to environmental concerns, they encounter significant obstacles, including a lack of institutional support and resources, sociocultural norms, and university power structures that marginalize their voices. Despite these challenges, students employ strategies such as building cross-institutional collaborations with NGOs, leveraging social media, and engaging in grassroots advocacy to navigate their bounded agency. The findings of this study contribute to a deeper understanding of the complex dynamics that shape the landscape for climate action efforts of student environmentalists in the Global South, highlighting the resilience and resourcefulness of student environmentalists in overcoming barriers to drive environmental sustainability.
Keywords: climate action; students; bounded agency; capability approach